Analisis Kajian Pustaka dalam Artikel Penelitian Tindakan Kelas: Pendekatan Systematic Literature Review - Kamila, Nayla Rizqi; Ahmad Nurohim; Wardah Agustina Fuadiyah; Linda Amelia; Imron Fauzi (Lembag, 2026)
Literature reviews play a crucial role in scientific research because they serve to integrate previous research findings to build a conceptual framework that supports new research. However, in the practice of writing Classroom Action Research (CAR) articles, previous research is often presented descriptively without adequate conceptual synthesis. This study aims to systematically analyze the practice of citing prior research in the literature review of CAR articles as part of a systematic literature review. The study employs a Systematic Literature Review (SLR) approach following the PRISMA 2020 guidelines, which include the stages of identification, screening, eligibility assessment, and literature synthesis. Literature sources were obtained from various academic databases such as Scopus, Web of Science, Google Scholar, and Crossref using keywords relevant to classroom action research and literature reviews. Data analysis was conducted through thematic analysis to identify patterns and trends in the writing practices of previous research in the literature review of classroom action research. The results indicate that literature review writing in action research articles is still dominated by a descriptive approach that presents previous research sequentially without adequate conceptual integration and thematic synthesis. Furthermore, critical evaluation of prior research methodologies remains limited, meaning that literature reviews do not yet fully serve as a foundation for developing the theoretical framework of the research. The findings highlight the importance of applying a systematic literature review approach in writing PTK literature reviews to produce a more analytical, systematic, and integrated synthesis of the literature.